Peran Kualitas Audit pada pengaruh Transfer Pricing dan Capital Intensity terhadap Tax Avoidance - Nugroho, Wawan Cahyo (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p14, 2022)
This study aims to examine the effect of transfer pricing and capital intensity on tax avoidance with audit quality as a moderating variable. This study uses a sample of 588 companies listed on the IDX in 2015-2020. Technical data analysts use Moderated Regression Analysis (MRA). The results of the study show that transfer pricing has no effect on tax avoidance. Capital intensity has a negative effect on tax avoidance. Audit quality is not able to moderate transfer pricing on tax avoidance. Audit quality strengthens the relationship between capital intensity and tax avoidance. Keywords: Transfer Pricing; Capital Intensity; Audit Quality; Tax Avoidance.